Influenza virus pandemics: past and future - Palese, Peter (Henry Stewart Talks, 2007)
Influenza virus, the agent and the disease, Epidemiology in humans and animals, The 1918 pandemic & reconstruction of the virus, Highly pathogenic avian influenza virus, Future influenza pandemics, Antiviral drugs against influenza, Influenza virus vaccine formulations (types & usage frequency)
Updated at 2015/01/19